2022
DOI: 10.3389/fnut.2022.859143
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Scores and Asthenoteratozoospermia Risk: Finding From a Hospital-Based Case–Control Study in China

Abstract: ObjectiveWe aimed to examine associations of diet quality scores, including the dietary approaches to stop hypertension (DASH), alternate Healthy Eating Index (AHEI), and Chinese Healthy Eating Index (CHEI) with asthenoteratozoospermia risk in China.MethodsAmong 254 cases and 633 controls in a hospital-based case–control study in Shenyang, Liaoning Province, China, DASH, AHEI, and CHEI were calculated using a validated food frequency questionnaire. Asthenotetrazoospermia was evaluated according to World Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Based on their findings, they recommended that clinical practitioners promote healthy eating habits as a means of improving semen quality. In a study of 254 cases and 633 controls, Cui et al ( 41 ) observed that higher scores on the Chinese Health Eating Index (CHEI), the Alternate Healthy Eating Index (AHEI), and DASH were associated with reduced asthenozoospermia risk. CHEI is used to evaluate diet quality according to the Dietary Guidelines for Chinese people, which recommend a high intake of cereal (especially whole grains), tubers, legumes, fruit, dairy products, soybeans, fish and shellfish, poultry, eggs, seeds, and nuts, and a low intake of red meat, cooking oil, sodium, added sugars, and alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their findings, they recommended that clinical practitioners promote healthy eating habits as a means of improving semen quality. In a study of 254 cases and 633 controls, Cui et al ( 41 ) observed that higher scores on the Chinese Health Eating Index (CHEI), the Alternate Healthy Eating Index (AHEI), and DASH were associated with reduced asthenozoospermia risk. CHEI is used to evaluate diet quality according to the Dietary Guidelines for Chinese people, which recommend a high intake of cereal (especially whole grains), tubers, legumes, fruit, dairy products, soybeans, fish and shellfish, poultry, eggs, seeds, and nuts, and a low intake of red meat, cooking oil, sodium, added sugars, and alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were required to complete a structured and self-administered health status questionnaire through face-to-face interviews by trained professional personnel. We further excluded participants with incomplete information (n = 70), an implausible total caloric intake (<800 or >4200 kcal/day) (n = 18), and history of varicocele (n = 3) ( Cui et al , 2022 ; Liu et al , 2022 ). Finally, 146 cases and 581 controls were eligible for the final analysis ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that there may be interactions among different types of phytochemicals, Model 3 was mutually adjusted for different types of phytochemical intake included in the study. Covariates for the final models were determined based on the correlation with phytochemical, clinical significance, and previous studies ( Wang et al , 2021 ; Cui et al , 2022 ; Zhao et al , 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dietary information was measured via a verified 110-item food frequency questionnaire (FFQ) at baseline, which was performed by experienced and well-trained personnel. The FFQ was designed to evaluate the frequency of dietary intake and supplement use over the past year before admission to the infertility clinic ( Cui et al , 2022b ; Huang et al , 2023 ), and its validity and reliability have been proved by our previous research ( Liu et al , 2021 ; Wang et al , 2021a ; Cui et al , 2022a ). The reproducibility coefficients were above 0.5 for most food groups, and Spearman correlation coefficients ranged from 0.3 to 0.7 for most food groups between weighed diet records and the FFQ ( Cui et al , 2022b ; Liu et al , 2022 ).…”
Section: Methodsmentioning
confidence: 99%